2019
DOI: 10.1017/wet.2019.108
|View full text |Cite
|
Sign up to set email alerts
|

Seed retention of winter annual grass weeds at winter wheat harvest maturity shows potential for harvest weed seed control

Abstract: Downy brome, feral rye, and jointed goatgrass are problematic winter annual grasses in central Great Plains winter wheat production. Integrated control strategies are needed to manage winter annual grasses and reduce selection pressure exerted on these weed populations by the limited herbicide options currently available. Harvest weed-seed control (HWSC) methods aim to remove or destroy weed seeds, thereby reducing seed-bank enrichment at crop harvest. An added advantage is the potential to reduce herbicide-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…have high seed retention at crop maturity. 8 Similarly, in Canada, problematic weeds of cereal, oilseed, and pulse crops, Setaria viridis (L.) P. Beauv., Chenopodium album L., and Bassia scoparia (L.) A. J. Scott, retain a high proportion of seed at crop maturity and thus are good candidates for HWSC control.…”
Section: Opportunities For Hwsc Use In North Americamentioning
confidence: 99%
See 3 more Smart Citations
“…have high seed retention at crop maturity. 8 Similarly, in Canada, problematic weeds of cereal, oilseed, and pulse crops, Setaria viridis (L.) P. Beauv., Chenopodium album L., and Bassia scoparia (L.) A. J. Scott, retain a high proportion of seed at crop maturity and thus are good candidates for HWSC control.…”
Section: Opportunities For Hwsc Use In North Americamentioning
confidence: 99%
“…19 In eastern Colorado, a high proportion (> 75%) of seed was retained by A. cylindrica and B. tectorum at wheat maturity. 8 In 2013, a field survey of winter wheat fields near Pullman, WA found that 58% of seeds of Lolium perenne L. ssp. multiflorum (Lam.)…”
Section: Weed Seed Retention Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…of their retained seeds might be reduced due to their stem growth type and seed set along the entire stem. Weed species of similar or taller height than the crop will increase the seed collection efficiency at harvest (Soni et al, 2019). It is also likely that some seeds spread and fall to the soil surface during the harvesting process.…”
Section: Potential To Target Weed Seeds With Hwscmentioning
confidence: 99%